In Keeping with Family Tradition: American Second-Wave Feminists and the Social Construction of Political Legacies - Foster, Johanna E. (Qualitative Sociology Review, 2018)
Through an interpretive lens that borrows from feminist postmodernist perspectives on identity and cognitive sociology, the manuscript utilizes in-depth interview data from 33 women active in the American second-wave feminist movement to explore how aging feminist activists construct their current political identities in relation to the meanings they give to the perceived progressive political identities and actions of their elders. In particular, this study examines the discursive strategies that respondents engage as they link their own feminist consciousness directly or indirectly to feminist, or otherwise progressive, parents and grandparents. Findings reveal three distinct political legacy narratives, namely 1) explicit transmission origin stories; 2) bridge narratives; and 3) paradox plots that add to both the social movement literature on the symbolic dimensions of recruitment, sustainability, and spillover, as well as cognitive sociological literature on the cultural transmission of political capital, in general, and to our understanding of American second-wave activists, more specifically.